(untitled) (Novateur Publications, 2025)
The purpose of this monograph is to develop and implement models and systems for ensuring the export of software products in order to develop modern forms of employment in the digital economy. The following tasks were set to achieve the set goal: Theoretical foundations of forms of employment in the context of digital transformation analysis and forms of remote service provision, study of foreign experience in the development of informal employment systems, the freelance market and digital platforms, ensuring modern employment improvement of the mechanism, organization of the labor market and remote work, prospective development of government and economic systems, development of G2B services for IT enterprises, prospects for the training of IT specialists and the formation of the institutional environment, modern methods and prospects of business process outsourcing and self-employment, models and methods of developing the BFA model and remote work forms It consists of developing algorithms. The Monography is intended for teachers, independent learners, students, masters, and doctoral candidates teaching in the field of digital economy and innovation.